Libraries, literacy & cultural harmony - Burrington, Gillian A. (ACURIL [S.l.], 1994)
Looks at the role played by public, school and academic libraries in supporting literacy and promoting cultural harmony. Makes suggestions of ways librarians can grasp opportunities to encourage cultural harmony.